Perfection the legal adjusting discipline of labour in the conditions of codification the labour legislation in Ukraine - Міщук, Михайло Олександрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article analyzes essence and features the discipline of labour. Made suggestions to the project of the Labour code in relation to the ways of perfection and systematization the legislation of discipline of labour